2013
DOI: 10.1140/epjc/s10052-013-2656-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutralino and chargino production in U(1)′ at the LHC

Abstract: We examine the production and decay modes of neutralinos and charginos in a softly-broken supersymmetric model with an extra Abelian symmetry U(1) ′ . We perform the study in a U(1) ′ model with a secluded sector, where the tension between the electroweak scale and developing a large enough mass for Z ′ is resolved by incorporating three additional SU(2) singlet fields into the model. Although the chargino sector is the same as in the MSSM, the neutralino sector of the model is very rich: five new fermion fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…This occurs across all 2 + E T , 4 + E T and 6 + E T signals and for all benchmarks. This confirms past analyses for 2 + E T [60,74], which indicated that, unless Z is leptophobic, and thus much lighter, the signal significance is small. However, that is not necessarily so at 27 or 100 TeV and across all signals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This occurs across all 2 + E T , 4 + E T and 6 + E T signals and for all benchmarks. This confirms past analyses for 2 + E T [60,74], which indicated that, unless Z is leptophobic, and thus much lighter, the signal significance is small. However, that is not necessarily so at 27 or 100 TeV and across all signals.…”
Section: Discussionsupporting
confidence: 88%
“…The symmetry-breaking sector of the model is very complex, and finding an acceptable minimum of the Higgs potential, even at the tree level, is non-trivial [60]. Once a minimum is found, the mass of the lightest Higgs boson can be fine tuned to 125 GeV by small variations in the parameterh s .…”
Section: The Secluded U(1) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In U(1) ′ models, the allowed Higgs mass ranges have to be reconsidered due to the additional quartic Higgs self-couplings from the D-terms. The masses obtained are generally larger, LEP bounds on Higgs bosons with SM-like couplings to the Z boson are easier to satisfy, and radiative corrections from top-stop loops as well as constraints from gauge coupling unification in different configurations for the Higgs spectrum can exist, and can satisfy the LHC bounds on the SM-like Higgs boson [34]. In what follows, we are concerned with the Higgs and neutralino sectors.…”
Section: U (1) ′ Modelmentioning
confidence: 99%
“…There, the absence of significant excesses of events is interpreted in simplified models, motivated by the SUSY particle content of the Minimal SUSY extension of the Standard Model (MSSM) and assuming simple branching ratios and relations among masses. Interpretations of the present constraints from the trilepton channel in realistic versions of the MSSM have been performed in [18][19][20][21] (see [22][23][24] for the rôle of trilepton final states in some beyond-the-MSSM models).…”
Section: Introductionmentioning
confidence: 99%